Pharmacogenomic Profiling of DPYD Mutations and Genotype‑guided Dose Adjustment to Prevent Fluoropyrimidine Toxicity in Gastrointestinal Cancer Patients: A Real‑world Study from North India - Paul, Davinder; Grewal, Gurvinder; Jain, Kunal; Pathak, Shuchita; Chhabra, Akanksha; Singh, Jagdeep; Singh, Suvir; -, Ramandeep; Sidhu, Manjinder Singh; Kaur, Barjinder (Asian Pacific Journal of Cancer Care, 2025)
Purpose: To quantify the prevalence of clinically actionable DPYD variants in North‑Indian gastrointestinal (GI) cancer patients and to evaluate whether Clinical Pharmacogenetics Implementation Consortium (CPIC)‑guided fluoropyrimidine dose attenuation mitigates early chemotherapy toxicity. Methods: We retrospectively reviewed 66 adults treated between January 2021 and December 2024 who underwent prescriptive DPYD genotyping for *DPYD* *2A*, c.2846A>T, *9A* (c.85T>C) and *13*. Fluoropyrimidine doses were modified according to CPIC activity‑score algorithms (25–50 % reduction for scores 1.5–1.0; ≥ 50 % reduction or avoidance for ≤ 0.5). Variant frequency was the primary end‑point; grade ≥ 3 toxicity within two cycles served as the secondary end‑point. Multivariable logistic regression identified independent predictors of toxicity. Results: Actionable variants were detected in 32/66 patients (48.5 %), dominated by *DPYD* *9A* (43.9 %). All carriers received genotype‑guided dose reduction. Overall grade ≥ 3 toxicity occurred in 13/66 patients (19.7 %): 17.6 % of wild‑type versus 21.9 % of variant carriers (P = 0.28). After adjustment, toxicity rates across gastrointestinal, hematological, and dermatological domains remained comparable. Diabetes mellitus emerged as the sole independent predictor of grade ≥ 3 toxicity (adjusted odds ratio 5.99, 95 % CI 1.19–30.3; P = 0.03). Conclusion: Almost half of North‑Indian GI‑cancer patients harbor an actionable *DPYD* variant—chiefly *9A*. Implementing CPIC‑based dose reduction neutralized variant‑linked excess risk of early severe toxicity, underscoring the clinical utility of routine DPYD genotyping and personalized fluoropyrimidine dosing. Enhanced vigilance is warranted for diabetic patients, who remain at heightened toxicity risk despite pharmacogenomic tailoring.